Artificial Neural Networks in Predicting the Number of New Students using the Backprobapication Method : (Case Study: Santo Thomas Catholic University Medan) - Alex Rikki; Doni El Rezen Purba; Marulak Lasron Siahaan; Petrus Leonardi Marpaung; Reni Maria Manalu (Institute of Computer Science (IOCS), 2022)
An artificial neural network is an information processing designed by imitating how the human brain works in solving problems, namely by carrying out the learning process. Backpropagation is one of the algorithms of artificial neural networks that is often used in predicting because it has a good level of accuracy. Uncertainty in the number of registrants at the Catholic University of Santo Thomas, forecasts or predictions are made. The problem formulation of this research is